Learner-centered teaching five key changes to practice - Weimer, Maryellen, 1947- (San Francisco : Jossey-Bass, 2013)
"In this new edition of the classic work, one of the nation's most highly regarded authorities on effective college teaching offers a comprehensive introduction to the topic of learner-centered teaching in the college and university classroom, including the most up-to-date examples of practice in action from a variety of disciplines, an entirely new chapter on the research support for learner-centered approaches, and a more in-depth discussion of how students' developmental issues impact the effectiveness of learner-centered teaching. Learner-Centered Teaching shows how to tie teaching and curriculum to the process and objectives of learning rather than to the content delivery alone"--
pt. 1. Foundations of the learner-centered approach -- pt. 2. The five key changes to practice -- pt. 3. Implementing the learner-centered approach.
Includes bibliographical references and indexes.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2021. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: College teaching; Learning, Psychology of; Electronic books